2021
DOI: 10.1002/tox.23334
|View full text |Cite
|
Sign up to set email alerts
|

Norcantharidin combined with paclitaxel induces endoplasmic reticulum stress mediated apoptotic effect in prostate cancer cells by targeting SIRT7 expression

Abstract: Prostate cancer (PCa), an extremely common malignancy in males, is the most prevalent disease in several countries. Norcantharidin (NCTD) has antiproliferation, antimetastasis, apoptosis, and autophagy effects in various tumor cells. Nevertheless, the antitumor effect of NCTD combined with paclitaxel (PTX), a chemotherapeutic drug, in PCa remains unknown. The cell growth, proliferative rate, cell cycle distribution, and cell death were determined by 3‐[4,5‐dimethylthiazol‐2‐yl]‐2,5 diphenyltetrazolium bromide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…CC is a malignant gynecological cancer with high morbidity and mortality globally 39–41 . Despite great advancement in the therapeutic approaches for CC in recent years, the median survival period of CC patients at advanced stages remains only 16.8 months 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…CC is a malignant gynecological cancer with high morbidity and mortality globally 39–41 . Despite great advancement in the therapeutic approaches for CC in recent years, the median survival period of CC patients at advanced stages remains only 16.8 months 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…In some cellular contexts, autophagy acts as a cell survival pathway that prevents tumor cells from inducing apoptosis in response to cancer therapy, whereas in other settings, prolonged stress and progressive autophagy may ultimately lead to cell death, either in concert with apoptosis, or as a backup mechanism 20,21,32,33 . TEM revealed that the accumulation of AO puncta, the formation of autophagosomes, and the increased LC3‐I/LC3‐II conversion all induced autophagy 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer, NCTC has been demonstrated to trigger apoptotic cell death, by activating mitophagy-mediated autophagy signaling ( 39 ). In prostate cancer cells, NCTD has been revealed to induce endoplasmic reticulum stress-mediated apoptosis via suppressing SIRT1 ( 40 ). However, NCTD has not been previously reported to induce ferroptosis in other cell types.…”
Section: Discussionmentioning
confidence: 99%